Fiscal, investment and export multipliers and the COVID-19 pandemic slowdowns uncertainty factor in the First Half of 2020 - Arkadiusz J. Derkacz (Risks, 2020)
The COVID-19 pandemic has caused a significant slowdown in the development of almost all economies in the world. In this context, the main goal of this research is to try to present changes in the value of fiscal, investment and export multipliers as a result of the COVID-19 pandemic. The research was conducted in selected European Union countries. They are France, Germany, Italy, Poland, Portugal and Spain. This research is based on the theory of effective demand. The values of feeds and leakages of total demand in the period from 2015 to 2020 were examined and calculated. On this basis, the individual multipliers of autonomous spending were analyzed and their changes in the first period of the COVID-19 pandemic were presented. The analyses led to a surprising conclusion: it found that the autonomous spending multipliers in some economies increased. This means that they have become 'security buffers' for the health of economies. This means that the increase in their value weakened the negative effects of changes in autonomous expenditure on gross domestic product.
Keywords: 330; principle of efficient demand; fiscal multiplier; investment multiplier; export multiplier; COVID-19 pandemic slowdowns; uncertainty